PENERAPAN PEMBELIAN TERSELUBUNG YANG DILAKUKAN ANGGOTA POLRI DALAM PENYELIDIKAN TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA - Enni Merita (Justici, 2022)
ABSTRACT The problem of drug abuse in Indonesia is currently felt in an alarming state. As an archipelagic country that has a strategic location, both in terms of economy, social and politics in the international world, Indonesia has participated in tackling the crime of drug abuse, namely with the enactment of Law Number 35 of 2009 concerning Narcotics. The research method used in this paper is normative juridical. This research approach uses a normative juridical approach. Normative juridical is used as the main approach in exploring laws based on statutory regulations, namely by studying and studying and examining theories, concepts and principles of legal norms. Covert buying implementation in the investigation of criminal acts of narcotics abuse by police Investigations with covert buying techniques do not carried out in an open way, so that it is prone to errors made by officers, such as officers who carry out investigations do not report the results of the investigation because of circumstances that are not possible, so that investigations carried out can make it less likely to find out the mistakes made or the condition of the officers.